-6x+4=-4x+2

Simple and best practice solution for -6x+4=-4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+4=-4x+2 equation:


Simplifying
-6x + 4 = -4x + 2

Reorder the terms:
4 + -6x = -4x + 2

Reorder the terms:
4 + -6x = 2 + -4x

Solving
4 + -6x = 2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
4 + -6x + 4x = 2 + -4x + 4x

Combine like terms: -6x + 4x = -2x
4 + -2x = 2 + -4x + 4x

Combine like terms: -4x + 4x = 0
4 + -2x = 2 + 0
4 + -2x = 2

Add '-4' to each side of the equation.
4 + -4 + -2x = 2 + -4

Combine like terms: 4 + -4 = 0
0 + -2x = 2 + -4
-2x = 2 + -4

Combine like terms: 2 + -4 = -2
-2x = -2

Divide each side by '-2'.
x = 1

Simplifying
x = 1

See similar equations:

| -6b+62=8b+6 | | 3x-3y+7=0 | | 17x-28x-12=21 | | Y+13.4=8.63 | | 2r+10=14 | | 3/5a=18 | | 18b-6= | | -1x+9=7x-5 | | x^6-4x^5+13x^4=0 | | z^4+4iz+10i=0 | | -16y+18=-30 | | (1/5)^(x-9)=5^(7x-5) | | -3+8x=-59 | | 75=25t+4.9t^2 | | 0.6(x-4)=12.0 | | 38a+21-20a=39 | | -1x-9=7x+5 | | 75=25*t+0.5*9.8*t^2 | | 9(x+4)+x=3(x+5)-8 | | -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x |

Equations solver categories